Effect of Maternal Anxiety during Third Trimester on Pregnancy Outcomes and Infants' Mental Health - Z Shayeghian; SK Rasolzadeh Tabatabaey; E Seddighi looye (Tehran University of Medical Sciences, 2008)
Background & Aim: The issue of children's mental health has been attracting widespread attention in recent years and the issue of parent-child mental health is particularly important. To investigate the effect of maternal anxiety on pregnancy outcome and also infants' mental health were the main purposes of this article. Methods & Materials: In this comparative study, a total of 40 pregnant women were selected using random sampling method from Imam Khomeini hospital. First, The women completed the Ketel anxiety questionnaire during the third trimester of their pregnancies. Based on the results, 20 women were allocated in the anxious mothers' group and the other 20 women were allocated in the calm mothers' group. Then, birth indicators were measured in both groups at the time of birth. Finally, infants' mental health indicators were measured using infants mental health measurement scale three months later. Data were analyzed using descriptive- inferential statistics (Chi-square and t-test) in SPSS. Results: The results showed that there were significant differences in anthropometric indexes between two groups (P<0.001). The rate of vaginal delivery was more in calm mothers than in the vexatious ones. Most of the calm mothers stated that they had wanted pregnancies. Mental health of the calm mothers' newborns were significantly higher than the mental health of the other group's newborns (P<0.001). Conclusion: These findings illustrated that maternal mental status could affect pregnancy outcomes at birth and infants' mental health third months after birth.   Key words: anxiety, infants' mental health, pregnancy outcome